Moiré-Based Interferometry for Magnification Calibration of Bitelecentric Lens System - Yi Zhou; Jiangping Zhu; Qinyuan Deng; Junbo Liu; Xinchun Si; Song Hu (IEEE Photonics Journal, 2015)
The bitelecentric lens system is widely used in many domains, such as 3-D measurements and tube inspection. The magnification calibration for such a system is a crucial problem for its further application in achieving precise measurements. However, it is difficult to obtain an accurate result using a general magnification calibration method. In this paper, the Moiré-based interferometry is demonstrated to accurately calibrate the magnification of bitelecentric lens system that increases the speed and precision of the measurement. Two special grating marks containing upper and lower parts with slightly different periods are designed to generate Moiré fringes. By analyzing the finally obtained Moiré fringes, the magnification could be determined through Fourier-based phase analysis and a phase unwrapping algorithm, and the further the deviation is from the theoretical value, the more obvious the differences between upper and lower periods will be. Both simulations and experiments are conducted to verify the feasibility and effectiveness of the proposed approach. Results indicate that the magnification could be calibrated at the accuracy of 0.4% with extraordinary sensitivity.